Insight into tick and flea species infesting the North African Hedgehog Atelerix algirus in Tunisia - Ghofrane Balti; Hajer Aounallah; Ahmed Ouni; Moufida Derghal; Adel Rhim; Jomaa Chemkhi; Ikram Guizani; Ali Bouattour; Souheila Guerbouj; Youmna M'ghirbi (International Journal for Parasitology: Parasites and Wildlife)
Hedgehogs are small wild mammals known to host various ectoparasites, including hard ticks and fleas, which can transmit vector-borne pathogens to humans and animals. We investigated the ectoparasites infesting 10 hedgehogs (Atelerix algirus) captured in northern Tunisia and found both ticks and fleas. Ectoparasite species were identified based on their morphological characteristics as well as using molecular methods via the partial amplification of the 16 S rRNA, the mitochondrial Cytochrome C Oxidase subunit I, and the 18 S rRNA genes. Four tick species were identified: Haemaphysalis erinacei, followed by Rhipicephalus sanguineus, Ixodes ventalloi, and Hyalomma aegyptium. Molecular analysis confirmed the presence of the subspecies Haemaphysalis erinacei turanica, with phylogenetic clustering suggesting a genetic relationship with tick populations in Algeria, Turkey, and China. Two additional flea species were identified: Archaeopsylla erinacei, the hedgehog flea, and Ctenocephalides felis, the cat flea, both known to be vectors of pathogens. We confirmed that hedgehogs were infested with Archaeopsylla erinacei maura, with the obtained sequences clustering closely with those previously reported in Spain. This genetic similarity may suggest a shared origin and indicate a wider geographic distribution for this subspecies. Our study underscores the importance of understanding the interactions between hedgehogs, ectoparasites, and their environments. Our findings may inform public health strategies and wildlife management, aiming to control ectoparasite populations and reduce the risk of the emergence of zoonotic diseases.